Minimum Wage Effects in the Longer Run - David Neumark; Olena Y. Nizalova (Institute for the Study of Labor (IZA), 2004)
Exposure to minimum wages at young ages may lead to longer-run effects. Among the possible adverse longer-run effects are decreased labor market experience and accumulation of tenure, lower current labor supply because of lower wages, and diminished training and skill acquisition. Beneficial longer-run effects could arise if minimum wages increase skill acquisition, or if short-term wage increases are long-lasting. We estimate the longer-run effects of minimum wages by using information on the minimum wage history that workers have faced since potentially entering the labor market. The evidence indicates that even as individuals reach their late 20?s, they earn less and perhaps work less the longer they were exposed to a higher minimum wage, especially as a teenager. The adverse longerrun effects of facing high minimum wages as a teenager are stronger for blacks. From a policy perspective, these longer-run effects of minimum wages are likely more significant than the contemporaneous effects of minimum wages on youths that are the focus of most research and policy debate.
Keywords: J38; J23; J22; 330; minimum wage; employment; hours; earnings; Mindestlohn; Arbeitsmarkt; Internationale Arbeitsmobilität; Vereinigte Staaten